Ptolemy I and the Transformation of Egypt, 404-282 BCE - McKechnie, Paul (Mnemosyne, Supplements, History and Archaeology of Classical Antiquity Ser, 2018)
Intro -- ‎Contents -- ‎Preface -- ‎List of Figures and Tables -- ‎Notes on Contributors -- ‎Introduction (McKechnie) -- ‎Chapter 1. Ptolemy I in Egypt: Continuity and Change (Thompson) -- ‎Chapter 2. The Greek Wars: The Fight for Egypt (McKechnie) -- ‎Chapter 3. Soter and the Calendars (Bennett) -- ‎Chapter 4. The Role of Coinage in the Political Economy of Fourth Century Egypt (Colburn) -- ‎Chapter 5. Pharaoh and Temple Building in the Fourth Century BCE (Minas-Nerpel) -- ‎Chapter 6. The Satrap Stele of Ptolemy: A Reassessment (Ockinga) -- ‎Chapter 7. Identity and Cross-cultural Interaction in Early Ptolemaic Alexandria: Cremation in Context (Landvatter) -- ‎Index of Names and Subjects.